N-Kirchhoff–Choquard equations with exponential nonlinearity. (September 2019) - Arora, R.; Giacomoni, J.; Mukherjee, T.; Sreenadh, K.
Abstract: This article deals with the study of the following Kirchhoff equation with exponential nonlinearity of Choquard type (see ( K C ) below). We use the variational method in the light of Moser–Trudinger inequality to show the existence of weak solutions to ( K C ) . Moreover, analyzing the fibering maps and minimizing the energy functional over suitable subsets of the Nehari manifold, we prove existence and multiplicity of weak solutions to convex–concave problem ( P λ, M ) below.